Ludwig’s Angina Resulting in Mortality: an Autopsy Case - Musayev, Jamal; Hasanov, Adalat; Baghirzade, Mahmud; Hasanova, Parvin (The Bulletin of Legal Medicine, 2020)
Ludwig’s angina (LA) is a form of cellulitis that bilaterally affects the sublingual and submandibular soft tissue above the mylohyoid diaphragm at the base of the mouth. Due to its complications, the mortality rate of up to 50% has declined up to 8% in recent years with modern treatment options. Due to its complications, the mortality rate of up to 50% has declined up to 8% in recent years with the contribution of modern treatment options. In this article, a case of LA resulting with death is presented with autopsy findings. In cases where phlegmon is opened with an intraoral incision, the risk of aspiration pneumonia should be taken into consideration. In order to detect LA and its complications, organs and soft tissues of the oral cavity, neck region and thoracic cavity should be carefully examined in autopsy cases.